2014
DOI: 10.11648/j.jim.20140303.12
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic and Environmental Determinants of Private Equity in Emerging Asia Market: The Application of Extreme Bounds Analysis

Abstract: Abstract:There is a great debate on the significance of the stable economic and well structure legal system on the commercialization, innovation and employment in modern economies. Private equity activities play a significant role in these three aspects. The purpose of this work is to investigate the macroeconomic and environmental determinants of private equity investment in nine major Asian countries. The estimations are based on a data set running from 2004 to 2013. Applying robust estimation techniques Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…This positive effect is statistically significant at 5 percent level of significance. These findings are supported by a priori expectation, modern portfolio theory, Neo-classical of investment behaviour and the findings of Groh and Liechtenstein (2010), Clarysse et al (2009), Aizenman and Kendall (2008), Kelly (2012), Cherif and Gazdar (2011), Fé lix et al 2013, Oino (2014), Bernoth and Colavecchio (2014) and Oni (2017. This result is inconsistent with the finding of Oino (2014). From our findings, a strong capital market creates a favourable environment for PE exits through initial public offerings and the provision of valuation data for Merger and Acquisition deals.…”
Section: Discussion Of Regression Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This positive effect is statistically significant at 5 percent level of significance. These findings are supported by a priori expectation, modern portfolio theory, Neo-classical of investment behaviour and the findings of Groh and Liechtenstein (2010), Clarysse et al (2009), Aizenman and Kendall (2008), Kelly (2012), Cherif and Gazdar (2011), Fé lix et al 2013, Oino (2014), Bernoth and Colavecchio (2014) and Oni (2017. This result is inconsistent with the finding of Oino (2014). From our findings, a strong capital market creates a favourable environment for PE exits through initial public offerings and the provision of valuation data for Merger and Acquisition deals.…”
Section: Discussion Of Regression Resultssupporting
confidence: 65%
“…Most research on the determinants of private equity activity has been on developed countries. Among them are the studies of Groh and Liechtenstein (2010), Kelly (2012), Aizenman and Kendall (2008), Clarysse, Knockaert, & Wright (2009), Guler and Guillé n (2010), Cherif and Gazdar (2011), Fé lix, Pires and Gulamhussen (2013), Oino (2014) and Bernoth and Colavecchio (2014). However, Oni (2017) conducted a study on the determinants of venture capital supply in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…These three variables are dependent variables for the measurement of VC investments in China. We choose the following explanatory variables in the regression models: GDP growth rate (Gompers and Lerner, 1998; Carvell et al , 2013; Onio, 2014; Ning et al , 2015), export-to-GDP ratio (Zhu and Kotz, 2011), the annualized consumer price index (Onio, 2014; Ning et al , 2015), the number of patent applications (Shao and Pan, 2011; Lahr and Mina, 2016) and the M2 to GDP ratio (Gompers and Lerner,1998). GDP growth rate is the annualized growth rate for the inflation-adjusted value of total goods and services produced by residents and non-residents in China in a given quarter.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Bonini and Alkan (2012) document the positive effects of a good sociopolitical and entrepreneurial environment on the development of venture industry around the world. Onio (2014) indicates that macroeconomic factors such as GDP growth, tax rate, inflation, stock market value and interest rate are robust determinants of private equity, a later-state VC, in Asian countries. Ning et al (2015) examine the macroeconomic drivers of VC investments in the USA and find that the venture industry favors good macroeconomic and public market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PE investors demand the satisfying level of investor protection, entrepreneurial management skills, capital market activity and establishment of supporting institutions such as M&A Boutiques, Banks, Lawyers, Consultants, Accountants, etc. Oino (2014) analyzed the relevance of macroeconomic and environmental determinants of PE investment across nine emerging Asian markets using the EBA approach on data spanning from 2004 to 2013. Confirming the findings of prior studies, he found the corporate tax rate, GDP growth, disclosure and investor protection to be robustly related to PE investment with a threshold of 60 percent.…”
mentioning
confidence: 99%